Design thinking mindset to enhance education 4.0 competitiveness in Malaysia - Suhaila Che Noh; Abdul Malek Abdul Karim (Institute of Advanced Engineering and Science, 2021)
Education 4.0 will be the next aspect of the curriculum since programming has been taught from the primary school level. Training 4.0 requires teachers to equip students with not only the knowledge and information but also encourage students to be able to process information, develop creative thinking, and acquire problem-solving skills. However, the competency of teachers to encourage creative thinking and problem-solving skills is still questionable. The purpose of this concept paper is to provide an understanding of the conceptual framework for enhancing the teachers’ competency to enhance creativity and innovation in fulfilling the desire of education 4.0. design thinking is an innovative method that places people right at the center of problem solving. It discusses the variables that may affect the quality of teachers in education 4.0 and presents a literature review of approaches that can contribute to the creation of effective teaching methods to develop successful students and satisfy the demands of the workforce for industrial revolution 4.0. It is found that teachers need to be competent to build students' skills in meeting a competitive and innovative workforce in the wake of the industrial revolution 4.0. There are seven dimensions in the design thinking mindset that teachers need to understand to meet the 4.0 education requirements.